Electroacupuncture Treatment Suppresses Transcription Factor IRF8 in Spinal Cord of Rats with Spared Nerve Injury - Ying Wang; Meng Xue; Yang-yang Xia; Qian Jiang; Zhi-hua Huang; Cheng Huang (Pain Research and Management)
Objective. Neuropathic pain with complex mechanisms has become a major public health problem that greatly impacts patients’ quality of life. Therefore, novel and more effective strategies against neuropathic pain need further investigation. Electroacupuncture (EA) has an ameliorating effect on neuropathic pain following spared nerve injury (SNI), but the underlying mechanism remains to be fully clarified. Interferon regulatory factor 8 (IRF8), a critical transcription factor, was reported to be involved in the modulation of neuropathic pain. Here, we focused on exploring whether 2 Hz EA stimulation exerts an inhibitory action on spinal IRF8 in SNI rats. Methods. In this study, SNI rats were treated with 2 Hz EA once every other day for 21 days. Paw withdrawal threshold (PWT) was applied to determine the analgesic effect of 2 Hz EA on SNI rats. The spinal IRF8 and CX3CRl expressions were detected with qRT-PCR and western blot, and immunofluorescence staining was used to evaluate colocation of IRF8 or CX3CRl with microglial activation marker CD11b in the spinal cord. Results. It was found that SNI induced significant elevation of spinal IRF8 and CX3CRl mRNA and protein expression. Additionally, immunofluorescence results showed that SNI elicited the coexpression of IRF8 with CD11b, as well as CX3CRl with CD11b in the spinal cord. Meanwhile, 2 Hz EA treatment of SNI rats not only reduced IRF8 and CX3CRl mRNA and protein expression, but also reversed the coexpression of IRF8 or CX3CRl with CD11b in the spinal cord, along with an attenuation of SNI-evoked mechanical hypersensitivity. Conclusion. This experiment highlighted that 2 Hz EA can inhibit IRF8 expression and microglial activation in the spinal cord of SNI rats. Hence, targeting IRF8 may be a promising therapeutic strategy for 2 Hz EA treatment of neuropathic pain.